Comparative study of structural steel and reinforced concrete construction methods : a Malaysian case study - Sim, Nee Ting; Wei, Kiet Hu (Universiti Malaysia Sarawak, 2013)
Structural steel construction is a rather common and frequently opted for construction method all around the world, especially in more developed countries. However, in Malaysia, steel construction is yet to be as popular, with the industry still greatly favoring traditional construction methods such as reinforced concrete construction. From this study, it is hoped that structural steel usage in Malaysia can be strengthened and all parties in the industry can take the time saving of construction aspect into more serious consideration when choosing their construction methods.